Penugasan Pekerjaan Karyawan di PT Perkebunan Nusantara IV Regional IV - Rangkuti, Fatimah; Rozi, Syamsida (Politeknik Negeri FakFak, 2024)
The human resources and management system department is one of the departments in the company that has an important role in managing the company. One thing that must be considered is the suitability of work between employees and the abilities possessed by each employee. When employees get jobs that match their abilities, the work can be completed more efficiently. The purpose of this study is to divide work to employees so that 1 job will be done by 1 employee using the application of Hall's Theorem. If each subset of the set satisfies the conditions of Hall's Theorem, then the theorem guarantees complete matching. Based on the application of Hall's Theorem, it was found that there was complete matching of the bipartite graph in this problem so that 1 job can be assigned to only 1 employee, namely SMS assigned to employee A, AR assigned to employee B, PSB assigned to employee C, ESGS assigned to employee D, PG assigned to employee E, PR by employee F, MK by employee G, and JSAP by employee H.